2014
DOI: 10.4103/0974-2069.140829
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of a microtransesophageal probe in neonates and young infants undergoing surgery for congenital heart disease

Abstract: Background:The larger size of the currently available transesophageal echocardiography (TEE) probes limits their use to relatively older infants undergoing cardiac surgery. In very young neonates and infants, epicardial echocardiogram is used to assess postoperative residual defects. Recently, a miniaturized microTEE probe compatible in neonates has been introduced for clinical use. We evaluated the use of this probe in small infants undergoing cardiac surgery.Materials and Methods:Thirty-three consecutive neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Rather, we aimed to convey that it is the standardization of the approach, and following of a protocol, that increases rates of visualization. With the development of the miniaturized transducers, 2324 which can be used in small neonates, and further advances in in technology, it may be that transesophageal echocardiography becomes preferable to e-echo. However, demonstration of adequate visualization of the vascular anatomy would need to be shown.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, we aimed to convey that it is the standardization of the approach, and following of a protocol, that increases rates of visualization. With the development of the miniaturized transducers, 2324 which can be used in small neonates, and further advances in in technology, it may be that transesophageal echocardiography becomes preferable to e-echo. However, demonstration of adequate visualization of the vascular anatomy would need to be shown.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these limitations, the microTEE system (S8–3t, Philips Healthcare) might be an attractive alternative. This probe provided good quality images in very small infants [ 15 ]. Additionally, it could be demonstrated that the intraoperative and postoperative use of the microTEE probe provides adequate accuracy albeit inferior image quality when compared with the paediatric multiplane TEE probe in infants [ 7 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A miniaturised microTEE probe (5.6 mm 32-element phased array transducer) is presently available for perioperative use for neonates. [ 22 ] Intracardiac echo (ICE) intravascular ultrasound transducer, an 8-Fr, 2.5-mm, 64-element crystal array is also available for use. The ICE probe must be advanced into the right atrium using an extra venous femoral approach (8 or 10 F), and cardiac images from inside the heart are imaged.…”
Section: Advances In Imagingmentioning
confidence: 99%